Membrane Stabilizing and Cytotoxic Activities of Different Kupchan Partitionates of Oroxylum indicum (L.) Vent. Leaf and Bark Extracts (Dhaka University Journal of Pharmaceutical Sciences, 2014)
Abstract not availableDhaka Univ. J. Pharm. Sci. 12(2): 181-183, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17625